Development of chitosan/pluronic F108/polyethersulfone (PES) nanofiltration (NF) membrane for oily wastewater treatment - Norzakiah, Hamzah; Rosiah, Rohani; Abdul Rahman, Hassan; Syazrin Syima, Sharifuddin; Mohd Hafez Mohd, Isa (2018)
This study discusses a new finding for nanofiltration membrane development using phase inversion technique whereby polyethersulfone (PES) polymer was added with surfactant and additive. This research focuses on the development of a membrane that is efficient in treating oily wastewater and reducing membrane's low permeation flux issues. Five PES nanofiltration membranes were synthesized with pluronic F108 surfactant and different amounts of chitosan additive for each formulation. Subsequently, the effect of adding surfactant and additive on membrane performance was studied. Results showed that the membrane with the optimal amount of chitosan gave the highest flux and the rejection of oily wastewater with up to 90%. In addition, Fourier transforminfrared (FTIR) spectroscopy technique was used to characterize and analyse the membrane's properties. Hence, the developed membranes were successfully characterized and proved to be a good treatment for oily wastewater.